EFFECT OF PGR ON CLONAL PROPAGATION OF MADHUNASHINI (GYMNEMA SYLVESTRE R. BR.) THROUGH ROOTED CUTTING - J. R. CHAVDA; B. S. DESAI; S. K. JHA; M. B. TANDEL; D. P. PATEL (The Bioscan, 2015)
Gymnema sylvestre is important medicinal plant having diverse medicinal potential. Under the present study effect of PGR was evaluated on growth and root quality of G. sylvestre. Auxin treatment had marked effect on all growth traits observed. IAA-1000 ppm showed the highest survival percentage (88.33 %) and took minimum days for 50% sprouting (19.67 days). Plant height at 30, 60, 90 and 120 DAP was also maximum in IAA-1000 ppm (8.67 cm, 47.83 cm, 111.07 cm and 117.91 cm, respectively). However, at 30, 60, 90 and 120 DAP, maximum number of branches / plant (0.50, 1.36, 2.27 and 3.67) and leaves / branch (2.67, 12.67, 30.27 and 38.87, respectively) found maximum in IBA 250 ppm + IAA 250 ppm. Maximum leaf area (24.09 cm 2 ) and root girth (7.69 mm) was recorded in IAA-500 ppm. T8 treatment i.e IBA 500 ppm + IAA 500 ppm recorded lengthiest main root length (25.69 cm). Overall IAA-1000 ppm showed better result for all observed parameters hence, it can be used for large scale propagation of G. sylvestre through cutting. Future research can be directed toward influence of auxin treatments on overall production of Gymnemic acid in rooted cutting.